Pengembangan Virtual Reality Chemistry Berbasis Kearifan Lokal Alam Kalimantan Tengah Untuk Meningkatkan Kemampuan 4C Mahasiswa - Anatasya, Violina; Putra, Nandito (FKIP Universitas Palangka Raya, 2024)
Practicum is an effective method used in learning to improve skills and deepen chemical concepts and theories. However, the main obstacle in the chemistry practicum process is the procurement process regarding the limitations of the tools and materials needed. One innovative solution to overcome this challenge is to utilize Virtual Reality (VR) technology, which allows students to understand the material through interactive simulations. On the other hand, Central Kalimantan has a wealth of local wisdom that can be used as a means to associate chemical concepts with daily life. Through this research, a Virtual Reality Chemistry Laboratory (VRCL) was developed that integrates elements of local wisdom in Central Kalimantan. The research method used in this study is development research (R&D) with the ADDIE model, with the initial step of conducting analysis. This study aims to evaluate the extent to which VRCL can improve students' understanding of chemical concepts and strengthen the connection between science and local culture. The results of this study are expected to make an important contribution to the development of more contextual and relevant learning methods for students. The use of Virtual Reality Chemistry Laboratory combined with the local wisdom of Central Kalimantan's nature aims to improve the 4Cs (Communication, Collaboration, Critical Thinking, and Creativity) skills of students in associating technology with local wisdom values. After going through the learning process using virtual reality media through VR headsets, students can practice the 4Cs skills in terms of focusing questions, observing, identifying assumptions, making conclusions, and determining actions.